Abdimas Perancangan Sistem Rantai Pasok Stok Ikan di CV. Indonesia Nature Miracle: Sistem Informasi Stock barang - Agung Kridoyono; Elvianto Dwi Hartono; Mochamad Sidqon; Anton Breva Yunanda; Danang Ario Wibowo (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This article is a journal devotion for society that doing by educational institution especially us as a lecture to implement the threefold missions of higher education known as tridarma college. Implementation technology for society at a software form to control stock and the quality of fish during in distribution. Labelling product by the quality of fish through a date and a form of fish. In the resolution of problems on cv indonesia miracle of nature , we did devotion in the form of recording the date information system goes off fish of container and is also the name the person in charge of quality control , so that it can be used to support of the qualities of fish and to create a awake the availability of fish. At this system informants determined based on the study the implementation of which is the management cv indonesia miracle of nature .Risk analysis and mitigation supply chain had an impact on sales and an inventory of goods , by the presence of the program hopefully can help companies in the application of the determination quality of product Keywords: website, Supply chain, CV indonesia Nature Miracle